ҚАРАҚАЛПАҚ МИЛЛИЙ ОЯНЫЎ ӘДЕБИЯТЫНДА ТӘРБИЯ ПРИНЦИПЛЕРИНИҢ СӘЎЛЕЛЕНИЎИ - Меңлибаева, А. (FAN va JAMIYAT, 2019)
The article is devoted to the study of one of the actual issues today – principles of education on the example of the literary works of t Karakalpak poets in the epoch of the national Rebirth.